Strengthening One Health in BARMM: Integrative Approaches to Human, Animal, and Environmental Health for Sustainable Community Resilience - Magna Anissa A. Aming-Hayudini; Mahmor N. Edding; Brenda A. Hussin; Safia E. Aming (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
Where formal medical–veterinary linkages are weak or nonexistent, as in BASULTA, zoonotic risks are commonly governed through informal institutional mechanisms that may be described as pragmatic “political settlements” operating at the local level. Health workers often use tacit and networked knowledge and culture-specific coordination—such as consultation with local animal handlers, traditional healers,barangay leaders (village heads), and environmental officers—to recognize disease patterns before they are reportable ZDs. Although undocumented, these informal mechanisms enable communities to adjust quickly in geographically isolated and resource-poor territories and are an indication of what De Vera (2022) refers to as negotiated governance in conflict-affected areas. Instead of these configurations being seen as deficits, One Health “policies on paper” should identify and incorporate them as realistic nodes for institutionalization. This may require mediation of community-based animal health workers, institutionalization of local reporting pathways into surveillance and multi-actor protocols that value experiential knowledge as much as technical expertise. Although mired at local scale by piecemeal efforts, embedding such locally adapted coping mechanisms into formal policy can shift One Health implementation in BARMM away from externally-driven models and towards context responsive modes of governance sensitive to everyday practices; while supporting a resilient system overtime.